Immunomodulatory Activity of Parijoto Fruit (Medinilla speciosa) on Macrophage Phagocytosis, Lymphocyte Proliferation, and IgG Production - Jannah, Asni F.; Winanta, Aji; Anggreani, Ira; Krisridwany, Annisa (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
Parijoto fruit (Medinilla speciosa) contains flavonoid compounds that are potentially immunomodulators because they increase macrophage phagocytosis activity and lymphocyte proliferation in vitro. This study aims to determine the phytochemical compound content of parijoto fruit and its potential as an immunomodulatory agent in vivo. Parijoto fruit was extracted using 70% ethanol solvent. The ethanol extract of parijoto fruit (EEPF) was qualitatively identified by phytochemical screening. The immunomodulatory activity test in vivo was conducted using BALB/c mice, which were separated into five groups: untreated, Phyllanthus niruri L. (PN) extract (positive control), and test groups (125mg/KgBW; 250mg/KgBW and 375mg/KgBW). The treatment duration was 18 days, with the induction of the hepatitis B vaccine on days 7 and 14. An immunomodulatory activity test was conducted on the 19th day, which included a macrophage phagocytosis activity test, lymphocyte proliferation, and measurement of IgG levels. The identification results showed that EEPF contains flavonoids, tannins, and saponins. Macrophage phagocytosis activity showed that EEPF increased macrophages' phagocytosis capacity (PC) and phagocytosis index (PI). EEPF increased lymphocyte proliferation activity and IgG levels, significantly different from control and not substantially different from positive control. Collectively, EEPF increases immunomodulatory activity in vivo.